Старообрядческая моленная и школа в причудской деревне Казепяэ - Шор, Татьяна (Slavistica Vilnensis, 2010)
The first evidence on the Kasepää village (Kazepe, ‘Kasepel’ in Russian), situated on the Lake Peipus shore between Varnja and Kallaste, is from 1582. Its population was mixed even at that time: there occur both Russian and Estonian names. A number of parish members came to Kasepää from the White Sea region (Belomorey) and brought icons of the Solovetsky school here. There were more than 500 Fedoseyans in the village in the early 1830s. They had their OWD worship house, built, as a local legend has it, in the mid-18th century. It was moved to another place in the 1820s. This was the only worship house in Estonia’s Peipus area, which remained unsealed in the age of repressions under Nicholas I. In 1860, the Orthodox priest M. Malein made an attempt to transport the dismantled worship house to Voronye, but met Old Believers’ resistance and was compelled to yield. In 1862, a community member Timofei Ivanovich Skorodumov financially supported the building of new worship house and donated it to the community.After the law of October 17, 1905 bad been ratified, the Kasepää community was legalized and on June 12, 1908 took the name of the Kasepää Old Believer community of the Old Pomorian concord of Yuryev district (uezd) of Livland Province. The entire population of Kasepää was 689 people, 542 of which were members of the Old Believer community. In 1916 in Kasepää the school for children-Old Believers has been opened